Super cool construction activities with Max Axiom - Enz, Tammy (Graphic library. Science and engineering activity., 2015)
Scientist Max Axiom presents step-by-step instructions for building a variety of structures and contraptions including an arch, a hydraulic drawbridge, and a freeway ramp. Includes color photographs, a glossary, and further resources.